Colorado Paper - Middle-Product Jig, with Adjustable and Automatic Discharges for the Middle and Lower Product - Edgar G. Tuttle (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1897)
The accompanying figures show a jig arranged for separating the middle product or middlings obtained in the concentration of certain ores, minerals, coal, etc. In the preparation for sizing, prior to jigging, of ore-bearing minerals, coal, etc., with their impurities, it is generally desirable to avoid reducing them to unnecessarily small sizes. Where the impurities adhere to the mineral particles or are disseminated through its mass, it is generally necessary to crush to such a fineness as will unlock the minerals from the gangue. If a considerable proportion of the material consists of mixtures of the minerals and gangue, each in large size, and a lesser proportion consists of a mixture of the two, in smaller sizes of various dimensions, it is not always desirable to reduce the whole to such size as would be required to liberate completely the pieces of ore and gangue in the finest mixtures. In such a case it is preferable to reduce all the material to such an